The Relationship Between Green Finance and Financial Distress - Basmar, Edwin; Campbell, Carl M.; Puryandani, Siti; Basmar, Erlin (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
An increase in green finance will only occur because of the banking intermediary function which can control financial distress. This research aims to measure banking financial distress in order to improve green finance, especially when macroeconomic pressure occurs. This research found that there was a negative period due to financial distress, resulting in a strong decline in green finance. These findings use the Ed Waves Index Development Model based on Bank Indonesia's quarterly financial reports from 2019 to 2023. The findings are categorized into 2 parts, the first part consists of periods 1, 3 and 5 showing a negative relationship with financial distress pressure with minimal response to green finance, while the second part consisting of periods 2 and 4 shows a positive relationship indicating that financial distress pressures respond optimally to green finance. This research contributes to banking financial activities in managing intermediary fluctuations in order to improve green finance in Indonesia.